2020
DOI: 10.1038/s41598-020-68665-0
|View full text |Cite
|
Sign up to set email alerts
|

MAF1 is a chronic repressor of RNA polymerase III transcription in the mouse

Abstract: Maf1 −/− mice are lean, obesity-resistant and metabolically inefficient. Their increased energy expenditure is thought to be driven by a futile RNA cycle that reprograms metabolism to meet an increased demand for nucleotides stemming from the deregulation of RNA polymerase (pol) III transcription. Metabolic changes consistent with this model have been reported in both fasted and refed mice, however the impact of the fasting-refeeding-cycle on pol III function has not been examined. Here we show that changes in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…When active, Maf1 directly targets the Brf1 subunit of TFIIIB and RNAPIII to inhibit transcription. In addition, in proliferating and differentiated mammalian cells, Maf1 chronically represses RNAPIII transcription to balance RNA synthesis with cellular demand ( 43 , 44 ). Thus, if the mechanism underlying MHV68 induction of pre-tRNAs involved antagonizing Maf1-dependent repression, we reasoned that cells lacking Maf1 should no longer display a difference in pre-tRNA levels between uninfected and infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…When active, Maf1 directly targets the Brf1 subunit of TFIIIB and RNAPIII to inhibit transcription. In addition, in proliferating and differentiated mammalian cells, Maf1 chronically represses RNAPIII transcription to balance RNA synthesis with cellular demand ( 43 , 44 ). Thus, if the mechanism underlying MHV68 induction of pre-tRNAs involved antagonizing Maf1-dependent repression, we reasoned that cells lacking Maf1 should no longer display a difference in pre-tRNA levels between uninfected and infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, functional studies of POLR3A mutations associated with POLR3-HLD have demonstrated transcriptional defects when introduced in both yeast and human cells (Choquet et al, 2019a ; Moir et al, 2020 ). Further research on molecular pathways and other POLR3 interactors will be valuable in determining whether suppression of upstream POLR3 inhibitors, such as MAF1 (Reina et al, 2006 ; Johnson et al, 2007 ; Bonhoure et al, 2020 ; Vorländer et al, 2020 ), are appropriate for future treatments. It is also possible that a small molecule screening approach could identify drugs for the treatment of specific molecular mechanisms, such as upregulation of complex assembly cofactors or signaling molecules for nuclear import of POLR3 (Cloutier and Coulombe, 2010 ; Lesniewska and Boguta, 2017 ; Willis and Moir, 2018 ).…”
Section: Polr3-related Leukodystrophy: Approaching Treatment Optionsmentioning
confidence: 99%
“…Maf1 is an mTORC1 effector that has significant roles in cancer biology [ 20 24 ]. Maf1 is phosphorylated by mTORC1 at certain Serine and Threonine to regulate RNA Polymerase III-dependent transcription of tRNAs, microRNAs and other small nuclear RNAs [ 7 , 25 , 26 ]. Inhibiting Maf1 expression can induce cancerous transformation in hepatocellular cells and Maf1 overexpression can suppress tumor growth in vivo [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%